Comparative Analysis of Erythrocyte, Leukocyte, and Platelet Indices through Examinations using Sysmex XN-3000 and Yumizen H2500 in Clinical Practice - Wardani, Yuniar Putri; Indrasari, Yulia Nadar; Amrita, Putu Niken Ayu; Fuadi, Muhamad Robi'ul (Universitas Airlangga, 2025)
Introduction: Examining erythrocyte, leukocyte, and platelet indices is critical for diagnosis, disease management, therapy selection, and monitoring. It is imperative to evaluate the hematology analyzer used for a complete blood examination, as each device possesses distinct specifications, methods, and technologies. This study aimed to compare complete blood count parameters, specifically the erythrocyte, leukocyte, and platelet indices, using Sysmex XN-3000 and Yumizen H2500. Methods: This cross-sectional study used blood samples from adult outpatients aged >18 years at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Samples were collected using purposive sampling, resulting in 100 blood specimens for complete blood count analysis. The examined variables included erythrocyte, leukocyte, and platelet indices, which were compared across two different instruments, i.e., Sysmex XN-3000 and Yumizen H2500. The data were analyzed using either the Spearman or Pearson correlation test (p<0.05). The Bland-Altman plotting was employed to assess the differences between variables, with a minimum of five agreed-upon outliers. Results: Significant correlations were observed across all parameters, except for the mean corpuscular hemoglobin concentration (MCHC), which showed limited agreement in the Bland-Altman analysis. The Pearson and Spearman analyses revealed a significant correlation in the parameters of erythrocytes (0.00), leukocytes (0.00), and platelets (0.00). The Bland-Altman plot indicated seven outliers in the average MCHC values from the two analyzers, demonstrating insufficient agreement. Conclusion: There is significant agreement and correlation in the erythrocyte, leukocyte, and platelet indices from both analyzers. This finding affirms the compatibility of both instruments for clinical use, with caution advised when interpreting MCHC values. Highlights: 1. This study evaluated the validity of different hematology analyzers for complete blood count examinations in medical laboratories, a topic that has rarely been discussed in detail. 2. The results of this study are expected to contribute to the quality improvement of medical laboratory technologies in Indonesia.